1989
DOI: 10.1042/bj2580187
|View full text |Cite
|
Sign up to set email alerts
|

Binding of FAD to 6-hydroxy-d-nicotine oxidase apoenzyme prevents degradation of the holoenzyme

Abstract: Expression of the 6-hydroxy-D-nicotine oxidase (6-HDNO) gene from Arthrobacter oxidans cloned into Escherichia coli showed a marked temperature-dependence. Transformed E. coli cells grown at 30 degrees C exhibited a several-fold higher 6-HDNO activity than did cells grown at 37 degrees C. This effect did not depend on the promoter used for expression of the cloned gene in E. coli, nor was it an effect of 6-HDNO mRNA instability at 37 degrees C. Studies performed in vivo and in vitro revealed that an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This phenomenon indicated that ETF:QO protein synthesis was not affected and should not be the cause of ETF:QO protein reduction. This, in vivo, indirectly confirmed the hypothesis of previous research, that the decrease in ETF:QO protein might possibly be due to a faster degradation of mutant ETF:QO proteins. The defective FAD binding to ETF:QO in RR‐MADD patients should be explained on the basis of a subtly altered protein structure that partially, but not entirely, hampers the affinity of FAD to flavoproteins.…”
Section: Discussionsupporting
confidence: 89%
“…This phenomenon indicated that ETF:QO protein synthesis was not affected and should not be the cause of ETF:QO protein reduction. This, in vivo, indirectly confirmed the hypothesis of previous research, that the decrease in ETF:QO protein might possibly be due to a faster degradation of mutant ETF:QO proteins. The defective FAD binding to ETF:QO in RR‐MADD patients should be explained on the basis of a subtly altered protein structure that partially, but not entirely, hampers the affinity of FAD to flavoproteins.…”
Section: Discussionsupporting
confidence: 89%
“…The steady-state levels of the mature SDH complex is lower when the covalent bond is disrupted either by mutation of the His 90 residue or by deletion of Sdh5. This is probably not caused by an impaired import or processing of Sdh1 [8]; rather, the possibilities include an increase in protease sensitivity [33] or an inherently less stable holo-complex in vivo that is prone to disassembly [32]. …”
Section: 0 Fad As a Cofactor In Complex IImentioning
confidence: 99%
“…The second step in the bacterial degradation of nicotine is catalyzed by 6‐HDNO, which was one of the first discovered covalent flavoproteins and has been extensively studied [41–43]. By incubating the apo form of 6‐HDNO with [ 14 C] FAD, it was shown that in vitro covalent flavinylation is a self‐catalytic process [44].…”
Section: ‐Hdnomentioning
confidence: 99%